Increased concentrations of bone sialoprotein in joint fluid after knee injury. Issue 9 (September 1996) - Lohmander, L S; Saxne, T; Heinegård, D
Abstract : OBJECTIVE: To detect evidence for localised changes in bone matrix metabolism after joint trauma and in post-traumatic osteoarthritis by quantification of bone sialoprotein in joint fluid and serum after knee injury in a cross sectional study. METHODS: Samples of knee joint fluid and serum were obtained from volunteers with normal knees (n = 19), patients with rupture of the anterior cruciate ligament isolated or combined with tear of a meniscus (n = 114), and patients with isolated meniscus lesions (n = 80). Concentrations of bone sialoprotein were determined by ELISA. Concentrations of other markers of joint tissue metabolism in these samples were determined in previous investigations. RESULTS: The median concentrations of bone sialoprotein in joint fluid from healthy volunteers was 122 ng ml-1 (range 41 to 183). Concentrations of bone sialoprotein were increased in both injury groups compared with the reference group (median for cruciate ligament injury 146 ng ml-1, range 72 to 339; median for meniscus injury 166 ng ml-1, range 75 to 376). After injury, bone sialoprotein increased quickly and remained increased for six months. Bone sialoprotein in joint fluid was increased only in samples from joints with normal or nearly normal (fibrillated) cartilage, and was within reference range in joints with radiographic signs of osteoarthritis. Bone sialoprotein concentrations in joints with cruciate ligament injury were positively correlated with levels of aggrecan and cartilage oligomeric matrix protein fragments, and with levels of stromelysin-1 and tissue inhibitor of metalloproteinase-1. The ratios between the concentrations of bone sialoprotein in joint fluid and serum were > 1 in the majority of the cruciate ligament injury cases. CONCLUSIONS: The release of significant amounts of bone sialoprotein into joint fluid in connection with acute joint trauma may be associated with injury to, and active remodelling of, the cartilage-bone interface and subchondral bone. The findings are consistent with dramatic shifts in cartilage, bone, and synovial metabolism following joint injury. Bone sialoprotein concentrations in synovial fluid may be a useful marker of subchondral injury and remodelling following joint injury.